Sistem Informasi Layanan Peserta Diklat Pada Balai Pelatihan Pertanian Jambi - Ngasiran, Ngasiran; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2023)
BAPELTAN Jambi is a provider of education and skills training for extension workers, officers and farmers/farming communities engaged in agricultural business, especially in the Jambi Province region, in its existence. So far, the Jambi Agricultural Training Center is still holding on training by using conventional methods, irregular document archiving, old data searches and data redundancy because it is processed with a simple application, namely Microsoft Excel and the training is done directty. It can be a serious problem, because the training is heldby using virtual meeting especially in this pandemic situation. So we need a new system to solve these problems. The BAPELTAN need a system which is ready to use directty in cyber network. The service information system for the participants of the Jambi agricultural training center is already desaign like LMS system because the participant are in the outside of Jambi City and training is held by using virtual meeting. The design of this online training system in this research uses UML tools and it is planned to apply by using the Moodle program. The description of system function is designed to be a prototype of the service information system for participants of the Jambi agricultural training center. The advantage of this design that is it can create a complete database to serve training participants in seeking insights at the Jambi agricultural training center. Training participants can upload evaluation documents, download training equipment needs, fill out training activity attendances and others so that the training participant's service information system is ready with the data and documentation which is needed by the training participants, teachers, admins, and the head of the center. This system can be accessed anywhere and anytime without any limitation for those who have registered to become participants.